Surface-induced crystallization in supercooled tetrahedral liquids - Li, Tianshu; Donadio, Davide; Ghiringhelli, Luca M.; Galli, Giulia (Nature Materials, 2009)
Surfaces have long been known to have an intricate role in solid-liquid phase transformations. Whereas melting is often observed to originate at surfaces, freezing usually starts in the bulk, and only a few systems have been reported to exhibit signatures of surface-induced crystallization. These include assembly of chain-like molecules2, some liquid metals and alloys3-5 and silicate glasses6,7. Here, we report direct computational evidence of surface-induced nucleation in supercooled liquid silicon and germanium, and we illustrate the crucial role of free surfaces in the freezing process of tetrahedral liquids exhibiting a negative slope of their melting lines (dT/dP|coexist >0). Our molecular dynamics simulations show that the presence of free surfaces may enhance the nucleation rates by several orders of magnitude with respect to those found in the bulk. Our findings provide insight, at the atomistic level, into the nucleation mechanism of widely used semiconductors, and support the hypothesis of surface-induced crystallization in other tetrahedrally coordinated systems, in particular water in the atmosphere. © 2009 Macmillan Publishers Limited. All rights reserved.
CRIS-Team Scopus Importer:2023-09-25